Sense Properties of Sentences in Descriptive Text Written by the Tenth Graders at SMA N 4 Magelang in the Academic Year 2017/2018 - Bilqis Tri Widya Ningrum (Faculty of Education and Teachers Training, 2018)
This study investigates sense properties of sentences in descriptive text written by the tenth graders at SMA N 4 Magelang in the academic year 2017/2018. The objectives of this research are to find out the sense properties of sentences are used and the most dominant sense properties of sentences is used in descriptive text. The type of this research is descriptive qualitative research. The researcher used descriptive text written by the tenth graders at SMA N 4 Magelang as the data source. The researcher employs documentation as the method of collecting data. In analyzing the data, the researcher describes the type of sense properties of sentences found in descriptive text by referring to the theory by Hurford and Heasley (1983). Based on the data analysis, there were 50 sentences of analytic sentence, 68 sentences of synthetic sentence, and 0 sentence of contradictory sentence from 118 sentences. In this research, the students mostly used synthetic sentence in their descriptive text.